Dominant dystrophic epidermolysis bullosa: identification of a Gly-->Ser substitution in the triple-helical domain of type VII collagen. - Christiano, A M (1994)
Epidermolysis bullosa (EB) represents a group of genodermatoses characterized by fragility and easy blistering of the skin. In the dystrophic forms of EB, blisters occur below the basement membrane of the skin, at the level of the anchoring fibrils. We have recently demonstrated tight genetic linkage between the type VII collagen gene (COL7A1) and both the dominant and recessive forms of dystrophic EB. We searched for mutations in dominant dystrophic EB by PCR amplification of genomic segments of COL7A1, followed by heteroduplex analysis. Examination of the PCR fragment corresponding to exon 73 of COL7A1 revealed a marked shift in the electrophoretic pattern in patients from a large Finnish dominant dystrophic EB family with genetic linkage to the COL7A1 locus (Z = 5.37, theta = 0). Sequence analysis revealed a G-->A transition at nucleotide 6118 in the triple helical domain of COL7A1, which converted a glycine residue to a serine (GGT-->AGT). This mutation occurs between interruptions 11 and 12 of the triple helix, in the seventh of a series of 24 uninterrupted Gly-Xaa-Yaa repeats. Pathogenetic glycine substitutions that disrupt the triple helix have been shown to exert a deleterious effect on the protein in several other disorders involving collagen genes. The clinical phenotype in this family probably arises due to a dominant negative mutation in type VII collagen, resulting in the formation of structurally abnormal anchoring fibrils.